2018
DOI: 10.1182/blood-2018-99-118088
|View full text |Cite
|
Sign up to set email alerts
|

Increasing CD28-FOXP3+CD8+ Treg and Senescent CD8+NK2GA+Eomes+ NK-like T Cells in Peripheral Blood of Patients with Multiple Myeloma

Abstract: Immune dysfunction in patients with multiple myeloma (MM) includes TGF-β induced dendritic cell dysfunction, regulatory T cell (Tregs)/Th17 cell imbalance, accumulation of Tregs and myeloid derived suppressor cells. These tumor-induced dysfunctions may contribute to immune escape and even suppress immune cells introduced in adoptive cellular immunotherapy. CD28 independent T cells of the effector memory (TEM) and CD45RA+ effector memory (TEMRA) population were shown to accumulate with age and contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Noteworthy, the presence of IFNg comes at the expense of an induction of PD-L1 on numerous stromal cell types, among them endothelial cells (199,200); this process is likely to counteract the beneficial effects of IFNgsecreting effector T cells which may be rendered dysfunctional (201). The infiltration of tumor sites by cytotoxic CD8 + T cells is usually correlated with a favorable clinical prognosis, however immunosuppressive conditions can polarize these cells to CD8 + FOXP3 + regulatory cells with similar immunomodulatory and angiogenic properties as CD4 + Tregs (202)(203)(204)(205). Studies of coronary artery disease and systemic sclerosis found T cells with angiogenic potential in blood samples of patients and demonstrated that these CD3 + CD31 + CXCR4 + cells (referred to as angiogenic T cells) play a vital role for the colony formation and differentiation of endothelial progenitor cells (EPCs) in the bone marrow (110,206).…”
Section: Immune Cells Are Mediators Of Angiogenesismentioning
confidence: 99%
“…Noteworthy, the presence of IFNg comes at the expense of an induction of PD-L1 on numerous stromal cell types, among them endothelial cells (199,200); this process is likely to counteract the beneficial effects of IFNgsecreting effector T cells which may be rendered dysfunctional (201). The infiltration of tumor sites by cytotoxic CD8 + T cells is usually correlated with a favorable clinical prognosis, however immunosuppressive conditions can polarize these cells to CD8 + FOXP3 + regulatory cells with similar immunomodulatory and angiogenic properties as CD4 + Tregs (202)(203)(204)(205). Studies of coronary artery disease and systemic sclerosis found T cells with angiogenic potential in blood samples of patients and demonstrated that these CD3 + CD31 + CXCR4 + cells (referred to as angiogenic T cells) play a vital role for the colony formation and differentiation of endothelial progenitor cells (EPCs) in the bone marrow (110,206).…”
Section: Immune Cells Are Mediators Of Angiogenesismentioning
confidence: 99%
“…(1) CD45RA + /FoxP3 + : Naïve T regulatory cells (2) CD45RA -/FoxP3 + : Non-T regulatory cells (3) CD45RA -/FoxP3 Bright Positive : Effector T regulatory cells With CD8/CD28/FoxP3, we can also identify CD8 T regulatory cells (Kasakovski et al, 2018).…”
Section: T Regulatory Cellsmentioning
confidence: 99%